Assessment of resident physicians satisfaction on residency training in Southwest China:A cross-sectional study - Lulin Chen; Yanting Zhou; Wei Liu (Clinical Epidemiology and Global Health)
Introduction: Chinese Resident Physician Standardized Training has been established to enhance medical training standards and physician capabilities since 2014. Studies indicate high rates of depression and low satisfaction among resident physicians, underscoring the need for surveys to inform policy and enhance their well-being. This study aimed to investigate the satisfaction of resident trainees in southwest China. Methods: A cross-sectional survey was conducted from February 2024 to March 2024 in 5 hospitals from 3 cities in southwest China, using convenience sampling to collect data from residents through a self-administered online questionnaire. The data including demographics, training perspectives, and suggestions was analyzed using SPSS 25.0 with Ordinal Logistic regression to identify factors influencing satisfaction. Results: The survey yielded 484 valid responses from 547 collected questionnaires, with an effective rate of 88.48 %. Participants were predominantly first-year residents, female, aged 26–30, and specialized in internal medicine, surgery, general medicine, and medical technology. The majority (78.93 %) expressed overall satisfaction with their residency training, but income satisfaction was lower at 64.05 %. Gender and neutral responses to certain aspects of training as predictors of dissatisfaction, including the training organized by the teaching management department, the training environment, the importance attached to residency training and the program's usefulness for future clinical work. Open-ended feedback from trainees highlighted the need for increased income, improved clinical training, and reduced workload. Conclusions: Our study found 78.93 % of residents satisfied with their training programs. Female residents and those with neutral views or income dissatisfaction were less satisfied. Increasing income, improving clinical training, and reducing workload could further boost satisfaction and program quality.